The new cultural history of Peronism power and identity in mid-twentieth-century Argentina - Karush, Matthew B. 1968-; Chamosa, Oscar (Duke University Press, 2010)
Populism, melodrama, and the market : the mass cultural origins of Peronism / Matthew B. Karush -- Peronists and cabecitas : stereotypes and anxieties at the peak of social change / Natalia Milanesio -- The Malón de la Paz of 1946 : indigenous descamisados at the dawn of Peronism / Diana Lenton -- Criollo and Peronist : the Argentine folklore movement during the first Peronism, 1943/1955 / Oscar Chamosa --Unforgettable kitsch : images around Eva Perón / Anahi Ballent -- Working-class beauty : queens under Peronism / Mirta Zaida Lobato, María Damilakou, and Lizel Tornay -- Peronism in "good taste" : culture and consumption in the magazine Argentina / Eduardo Elena -- Political emotions and the origins of the Peronist resistance / César Seveso